Sub-millimeter size high mobility single crystal MoSe2 monolayers synthesized by NaCl-assisted chemical vapor deposition. Issue 3 (8th January 2020) - Li, Juncheng; Yan, Wenjie; Lv, Yanhui; Leng, Jian; Zhang, Duan; Ó Coileáin, Cormac; Cullen, Conor P.; Stimpel-Lindner, Tanja; Duesberg, Georg S.; Cho, Jiung; Choi, Miri; Chun, Byong Sun; et al.
Abstract : Sub-millimeter single crystal MoSe2 monolayers with a mobility of 38 cm 2 V −1 s −1 and responsivity of 42 mA W −1 were synthesized by NaCl-assisted chemical vapor deposition. Abstract : Monolayer MoSe2 is a transition metal dichalcogenide with a narrow bandgap, high optical absorbance and large spin-splitting energy, giving it great promise for applications in the field of optoelectronics. Producing monolayer MoSe2 films in a reliable and scalable manner is still a challenging task as conventional chemical vapor deposition (CVD) or exfoliation based techniques are limited due to the small domains/nanosheet sizes obtained. Here, based on NaCl assisted CVD, we demonstrate the simple and stable synthesis of sub-millimeter size single-crystal MoSe2 monolayers with mobilities ranging from 38 to 8 cm 2 V −1 s −1 . The average mobility is 12 cm 2 V −1 s −1 . We further determine that the optical responsivity of monolayer MoSe2 is 42 mA W −1, with an external quantum efficiency of 8.22%.